Cell-bound complement activation products in antiphospholipid antibody-positive patients without other systemic autoimmune rheumatic diseases - Erkan, Doruk; Vega, Joann; O’Malley, Tyler; Concoff, Andrew (Frontiers in Immunology, 2024)
The objective of this study was to analyze complement activation in aPL-positive patients without other systemic autoimmune rheumatic diseases, using C3/C4 and cell-bound complement activation products (CB-CAPs) (B-lymphocytes [BC4d], erythrocytes [EC4d], and platelets [PC4d]). Persistently aPLpositive patients with or without aPL-related clinical manifestations (thrombotic APS [TAPS], microvascular APS [MAPS], obstetric APS, thrombocytopenia [TP], and/or hemolytic anemia [HA])were enrolled in a single center study. Blood and clinical data were collected at baseline; a subgroup of patients completed 6-or 12-month follow-up. At baseline, 4/31 (13%) patients had decreased C3/C4, while 7/29 (24%) had elevated BC4d, 11/33 (33%) EC4d, and 12/32 (38%) PC4d. Based on different aPL profiles, all patients with decreased C3/C4 or elevated BC4d, EC4d, and PC4d had triple aPL or isolated lupus anticoagulant positivity. Based on different aPL clinical phenotypes, the number of patients with strongly positive EC4d and PC4d were proportionally higher in those with MAPS/TP/HA, compared to TAPS or no APS. Compared to baseline, the frequencies of BC4d, EC4d, and PC4d positivity were not significantly different in the subgroup of patients during their 6-or 12-month follow-up. There was a weak correlation between C3/C4 and CB-CAPs, especially for PC4d. In summary, complement activation in aPL-positive patients varies based on aPL profiles and clinical phenotypes. Given the higher percentage of aPL-positive patients with abnormal CB-CAPs, compared to C3/C4, and the poor inverse correlation between CB-CAPs and C3/C4, our study generates the hypothesis that CB-CAPs have a role in assessing disease activity and thrombosis risk in aPL-positive patients.